2020
DOI: 10.1021/jacs.0c08948
|View full text |Cite
|
Sign up to set email alerts
|

Axially and Helically Chiral Cationic Radical Bicarbazoles: SOMO–HOMO Level Inversion and Chirality Impact on the Stability of Mono- and Diradical Cations

Abstract: We report persistent chiral organic mono-and diradical cations based on bicarbazole molecular design with an unprecedented stability dependence on the type of chirality, namely axial versus helical. An unusual chemical stability was observed for sterically unprotected axial bicarbazole radical, in comparison with monocarbazole and helical bicarbazole ones. Such results were experimentally and theoretically investigated, revealing an inversion in energy of the singly occupied molecular orbital (SOMO) and the do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 79 publications
(162 reference statements)
5
57
0
Order By: Relevance
“…1), SOMO-HOMO inversions exist in the gas phase but do not exist in polar solvents, such as water, and when using density functionals that account for dispersion (15)(16)(17). We and others found that in π-conjugated radical cations, the SOMO-HOMO inversions tend to persists in polar solvents (19,21,22). We now study SOMO-HOMO inversions in radical cations using the more reliable, long range-and dispersion-corrected UwB97xD functional [38], in conjunction with the PCM solvent model for water.…”
Section: Dft Computationsmentioning
confidence: 94%
See 1 more Smart Citation
“…1), SOMO-HOMO inversions exist in the gas phase but do not exist in polar solvents, such as water, and when using density functionals that account for dispersion (15)(16)(17). We and others found that in π-conjugated radical cations, the SOMO-HOMO inversions tend to persists in polar solvents (19,21,22). We now study SOMO-HOMO inversions in radical cations using the more reliable, long range-and dispersion-corrected UwB97xD functional [38], in conjunction with the PCM solvent model for water.…”
Section: Dft Computationsmentioning
confidence: 94%
“…Typically, the inversion is associated with improved stability of the radical (vide infra, EPR spectroscopy section) (16)(17)(18)(19)21), and a triplet ground state with significant ΔE ST in the corresponding diradical dication that is formed upon oneelectron oxidation radical cation (13,21,22). For 2 2•2+ -H 8 , triplet ground state with a significant ΔE ST is computed and for 2 2•2+ -TMS 8 , singlet ground state is predicted (Tables 1 and 2); these results correspond to SOMO-HOMO inversion in 2 •+ -H 8 and absence of it in 2 •+ -TMS 8 .…”
Section: Dft Computationsmentioning
confidence: 99%
“…Considering these concepts, we envisioned to develop a chiral luminescent exciplex with CP‐TADF property based on a judiciously selected chiral donor molecule, i. e. the C 2 ‐symmetric bicarbazole system, 1 [12] . This system presents a suitable donor ability, as indicated by its oxidation potential of 0.9 V vs. SCE and its high optical gap (E 00 =3.1 eV), to promote photoinduced electron transfer reaction with different electron acceptor units [10,11] .…”
Section: Resultsmentioning
confidence: 99%
“…There are many cases where SHC is supported by both experimental results and DFT calculations. [3,20,26,[28][29][30] Also, some researchers have studied the functional dependency of SHC in DFT calculations and they reported that the unusual electronic configuration is maintained with various functions. [4,37] Thus, DFT is considered to give reliable results about SHC.…”
Section: Discussionmentioning
confidence: 99%
“…11). [28] DFT calculations at the PBE0/def2-SV(P)/PCM (CH 2 Cl 2 /MeCN) level of theory suggested the occurrence of SHC in the radical cations 4 þ and 5 þ . CV measurements on compound 4 showed the first full reversible oxidation.…”
Section: Chiral Bicarbazole-based Radicalsmentioning
confidence: 99%